A agroindústria canavieira do Paraná: evolução histórica e impactos sobre o desenvolvimento local - Carvalheiro, Elizângela Mara (2005)
The work has as mark to analyze the main aspects of the historical evolution of the sugar cane agribusiness paranaense from his/her origin to the days today. Thus, the development of the sugar cane activity and some formations of the agribusiness paranaenses dress a to leave of a wide horizon, considering the aspects political, economical, social ecological of and, to the of it provided Paraná a prominence position any national of scenery, being just overcome by the of State São Paulo. Corollary of the, four points stand out: The first refers the historical of reconstruction of the process of installation of the productive units, in that it is verified that to suck cane production contributed to change the economical atmosphere and of the regions where he cultural settled. Of the second is of according to the fact that the companies to the noticed in the certain municipal district, they join to series of transformations, be ambient social or economical, generating the process of the vocation inhabitant's substitution. Of that forms, the municipal districts holders of the productive units, majority of yours of in they live the type of productive dependence of the suck cane agribusiness. The third display that before he makes process of development of the agribusiness and the crescent process of modernization/industrialization of the agriculture, what is verified any to suck cane of scenery is the group of changes it goes the involved agents any productive of process, what can be noticed, above all, through the production relationships that it is configured the to leave of the expansion of the busy areas with one of culture sugar cane. Already the fourth refers to generated transformations of the ambient social. In if treating of the factories and distilleries, it is noticed an occurrence of an intransigent one and it force hard-working oppression of the sober, and, manners of the cane cutters special, sober, live that, the day of each, an uncertainty of the maintenance of his work, that once and goes all of adds to suck mill owners of the they plows, once and goes all of each, looking is the mechanization adoption in the agricultural area and, even of until, adds machines of the one of introduction any cane of the one of cut.